Developing Augmented Reality-Based Learning Media to Overcome Fourth-Grade Elementary School Students’ Misconceptions Regarding the Ice Melting Phenomenon - Choirunnisa, Intan Oktavia; Anggoro, Subuh (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This study aims to create learning media using ice melting materials for the fourth-grade students and test the effectiveness of the learning media in learning science. This research is conducted by Research and Development (R&D) method with ADDIE model. The population studied is the student of the grade IV students in Banyumas Regency Elementary School. The instruments in this study are in the form of expert validation sheets, conceptual understanding tests in the form of pre and posttests, and documentation. The data analysis techniques used were Wilcoxon Signed Rank Test and N-Gain analysis. Based on the research results, the media used in this study is a learning media based on AR can be seen as a media that can increase the conceptual understanding of students in the phenomenon of the melting of ice. The average N-Gain score is 0.77, which represents a significant improvement in learning outcomes and is considered high. The results of these findings indicate that the Augmented Reality based learning media has been developed successfully in reducing student misconceptions and increasing students' understanding of the material submitted.